Spatial Analysis of Land use in Qibah County from 1993 to 2023 - Mujalli, Ahmed Ali; Al-Nosaiyan, Abdulrahman Suleiman (Journal of Humanities & Social Sciences, 2025)
This study contributes to providing valuable insights into land uses in Quba Center and offering effective strategies for improving urban planning and sustainable development. The spatial analysis of land use in the Quba Centre over a period of thirty years, highlighting changes in usage patterns and their impacts, showed that the area allocated to agricultural land decreased from 2.67% in 1993 to 0.61% in 2003, before rising again to 3.6% in 2023, highlighting the need for strategies to preserve this land as part of the main economic activity in the center. In addition, the area allocated to barren land decreased from 92.54% in 1993 to 74.9% in 2023, requiring sustainable planning to preserve the environment. Commercial and service activities also witnessed significant growth, with the area allocated to commercial uses increasing from 0.68% in 2003 to 1.2% in 2023, indicating improvements in infrastructure and meeting community needs. The study also indicated an increase in the area allocated to sports and recreational use, which increased from 1.6% in 2013 to 2.8% in 2023, reflecting the importance of recreational facilities in improving the quality of life. The results also showed major problems related to the lack of health, education and recreational services. The study recommended the need to develop urban planning strategies in line with population growth and urban expansion, while encouraging housing projects that include commercial and service areas to enhance access to facilities. The need to support commercial and service activities to increase jobs and improve economic sustainability.
Keywords: Analysis; Land Use; Dome Center